The Environmental Regimes Fragmentation: Towered Legal Taxonomy - Thajb, Ali Sadik; Mohd Anuar, Haslinda; Ayub, Zainal Amin (UniversityPublications.net, 2019)
It is widely known that there has been a large expansion in the international environmental law thus making it a unique branch of international law. A few environmental regimes have arose in the sub-fields, each with their own purpose and operating individually such as hazardous waste, air pollutants, biodiversity and many others. Such expansions arose in response to the degradation of the environment, but in spite of international efforts the international environmental regimes have to deal with diverse rules, efforts and applications. Academicians refer to it as fragmentation and as such the focus of this article is on the special types of environmental fragmentation. This article also builds a legal taxonomy that offers a notion that environmental laws are workable in many areas for academicians and environmental law experts are able to identify them